2005
DOI: 10.1103/physreva.71.033401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recombination in high-order harmonic generation in molecules

Abstract: We show that the dependence of high-order harmonic generation (HHG) on the molecular orientation can be understood within a theoretical treatment that does not involve the strong field of the laser. The results for H2 show excellent agreement with time-dependent strong field calculations for model molecules, and this motivates a prediction for the orientation dependence of HHG from the N2 3σg valence orbital. For both molecules, we find that the polarization of recombination photons is influenced by the molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 14 publications
3
45
0
Order By: Relevance
“…However, N 2 minima do not follow any simple pattern. This fact has been noticed earlier by Zimmermann et al [97]. This clearly indicates that the two-center interference model is not guarantied to work a priori.…”
Section: Validity Of the Two-center Interference Modelmentioning
confidence: 51%
“…However, N 2 minima do not follow any simple pattern. This fact has been noticed earlier by Zimmermann et al [97]. This clearly indicates that the two-center interference model is not guarantied to work a priori.…”
Section: Validity Of the Two-center Interference Modelmentioning
confidence: 51%
“…Yet the two-center interference minimum, though theoretically predicted [28,29], has never been observed experimentally [10,23,30]. We explain the lack of a two-center interference minimum in terms of laser-induced orbital distortion.…”
Section: Introductionmentioning
confidence: 81%
“…Two-center interference [13] has also been discussed by Zimmermann et al [28] and Gühr et al [29]. Zimmermann et al observed that the 3σ g orbital of N 2 is a linear combination of p and s orbitals at the two atomic centers.…”
Section: Introductionmentioning
confidence: 84%
“…With the REME and Rydberg orbital considered, we propose a model that has two major differences compared to earlier work by Lein et al [13] and by Zimmermann et al [28]. (i) Since we identify the Rydberg orbital (2pσ u ) rather than the HOMO (2pσ g ) as the MO for recombination, the destructive interference requires the free-electron plane wave to have a π phase difference between the atomic centers, rather than a difference of 2π , i.e.,…”
Section: Interference Models Involving Rydberg States To Explainmentioning
confidence: 90%